Framework for the optimization of online computable models. Issue 3 (2014) - ,; ,; ,; ,
Abstract : Purpose – The purpose of this paper is to make easily accessible models to test and compare the optimization algorithms we develop.Design/methodology/approach – For this, the paper proposes an optimization framework based on software component, web service, and plugin to exploit these models in different environments.Findings – The paper illustrates the discussion with optimizations in Matlab™ and R (www.r‐project.org) of a transformer described and exploitable from the internet.Originality/value – The originality is to make easy implementation of simulation model and optimization algorithm coupling using software component, web service, and plugin. Acknowledgements : The authors wish to thank Pierre‐Yves Gibello and Victor Soares for web server development.